Understanding adolescent stress and coping through psychodynamic constructs: evidence from a comparative study - Akın, Aslı; Goth, Kirstin; Seiffge-Krenke, Inge; Sarrar, Lea (Frontiers in Psychology, 2025)
IntroductionAdolescence is a critical developmental phase marked by increased vulnerability to stress and the formation of functional or dysfunctional coping strategies. While stress and coping are well-studied for their psychopathological relevance, their associations with psychodynamic constructs—such as impairments in personality structure, psychodynamic conflicts, and defense mechanisms-remain underexplored. This study investigated whether these psychodynamic features are associated with stress perception and coping styles among adolescents with and without mental health problems.MethodsA total of 171 adolescents (aged 14–21) completed standardized self-report measures assessing stress across multiple life domains, coping styles, psychodynamic conflicts, impairments in personality structure, and habitual defense styles. Mental health problems were screened via self-reports, and participants were classified into clinical and healthy control groups accordingly.ResultsAdolescents with mental health problems reported significantly higher stress and more dysfunctional (avoidant) coping strategies than their healthy peers. Regression analyses revealed that impairments in personality structure—particularly in identity and attachment—predicted heightened stress perception and dysfunctional coping, especially in the clinical group. Psychodynamic conflicts showed domain-specific links to stress: the guilt conflict was associated with school- and family-related stress, while the passive oedipal conflict predicted stress in romantic relationships. Maladaptive defense style was negatively associated with self- and peer-related stress, suggesting dissociative and affect-isolating mechanisms limiting conscious stress perception. Among healthy adolescents, functional (active) coping was associated with fewer impairments in attachment.DiscussionFindings highlight the value of psychodynamic constructs for understanding adolescent stress and coping and the relevance of attachment- and personality structure-focused prevention and intervention strategies.